TO MET OR NOT TO MET: THAT IS THE QUESTION!. Issue 2 (1st June 2013) - Sulistio, M; Vo, A; Franco, M
Abstract : Background: The Medical Emergency Team (MET) aim to identify clinically deteriorating patients to provide early intervention and prevent negative outcomes. However, for a proportion of these patients (ie, patients who are expectedly dying) continued intervention is 'medically futile' and unwanted by the patient and/or next-of-kin. Although diagnosing dying can be complex and challenging, it is an important step to establish appropriate goal of care, avoid futile medical intervention and allow a 'good death'. Aim: To determine the incidence of MET or Code Blues on patients who were expectedly dying. To identify patient's, clinician's or institution's variables that result in the occurrence of such incidents Methods: Retrospective 3 months audit of MET and code blue occurring on all Southern Health inpatients with onsite access to ICU support (Monash Medical Centre Clayton, Jessie McPherson Private Hospital, and Dandenong Hospital). Medical records were reviewed to collect patient demographics, admission and incident details, existing life limiting diagnosis, resuscitation and limitation of medical therapy status, clinical observations that may suggest terminal phase $, and documentation of communication with patient's next-of-kin. Results: A total of 456 incidents on 351 adult patients are analysed. Conclusion: A significant proportion of MET (10%) in a major hospital network may have been avoided if dying patients were better identified and the documentation of the goals of care was clearer. More such incidents occurred out of business hours than within hours. These results should encourage prospective study into what further measures could reduce this proportion of incidents.